2022
DOI: 10.56093/ijas.v92i5.124805
|View full text |Cite
|
Sign up to set email alerts
|

Potting substrate effect on yield and quality of strawberry (Fragaria × ananassa) in terrace gardening

Abstract: Terrace gardening or rooftop gardening is becoming popular in urban and peri-urban areas of metro cities worldwide including in India. Among various crops suitable for growing in terrace garden, strawberry is a popular one as being an important annual herbaceous plant with delicious fruits which can be easily grown in pots or containers including grow bags filled with different pottingsubstrates. In the present study, different combinations of soil, organic manure (vermi-compost and FYM) and cocopeat were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…Maher et al [13] revealed that perlite (75 %) + cocopeat (25 %) + jeevambrit resulted in a maximum fruit yield per plant. Similar findings have been reported by [15], [22] and [16].…”
Section: Effect Of Container Types and Potting Media On Yield Parameterssupporting
confidence: 92%
See 1 more Smart Citation
“…Maher et al [13] revealed that perlite (75 %) + cocopeat (25 %) + jeevambrit resulted in a maximum fruit yield per plant. Similar findings have been reported by [15], [22] and [16].…”
Section: Effect Of Container Types and Potting Media On Yield Parameterssupporting
confidence: 92%
“…A similar result was reported by Hassan et al [21] that utilizing coconut husk resulted in the largest plant height in strawberry, whereas soil cultivation produced the lowest. Kumar et al [22] indicates that highest plant height, was significantly recorded in Winter Dawn than Sweet Charlie in the potting substrates which consist of soil, vermicompost and cocopeat. Similar result was reported by Sharma et al [16] that highest plant height was recorded in the plant grown in PVC pots with a growing media of cocopeat, perlite and vermicompost in the ratio of 2:1:1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in this case, "Monterey" showed a significant sensitivity to water shortage at W60 compared to W100 (Table 2). As already described [47,48], water shortages tended to influence the vegetative structure of the plants, indicated by the lower plant height and leaf number, possibly leading to a reduction in photosynthesis [49]. Therefore, when the water supply is low, the plant's habit is more compact.…”
Section: Vegetative Parametersmentioning
confidence: 80%
“…Riso et al (2004) observed that the phytochemicals in tomatoes, in particular lycopene, reduces reactive oxygen species (ROS), thus avoiding cellular damage; however, several other mechanisms of healthy carotenoid action have been suggested (Krinsky and Johnson, 2005). With lower water availability, a higher ascorbic acid content was found during fruit ripening (Kumar et al, 2012). In a study conducted by Helyes et al (2014), the β-carotene level was positively influenced by water stress.…”
Section: Conflict Of Interestmentioning
confidence: 99%